Istota zjawiska private equity/venture capital (przykład Polski) - Jabłoński, Sebastian; Waszkiewicz, Maciej (The Nature of Private Equity/Venture Capital, 2007)
The publication elaborates the nature of private equity/venture capital. The article consists of two chapters. First one covers the history of expanding private equity/venture capital in the Emerging Markets, where the authors present the overview as well as they attempt to define clearly the term of PE/VC. The second part focuses on identifying the objectives and explaining the function and the mechanism of private equity/venture capital funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 135-144